Research progress on detection techniques for point-of-care testing of foodborne pathogens - Liu, Sha; Zhao, Kaixuan; Huang, Meiyuan; Zeng, Meimei; Deng, Yan; Li, Song; Chen, Hui; Li, Wen; Chen, Zhu (Frontiers in Bioengineering and Biotechnology, 2022)
The global burden of foodborne disease is enormous and foodborne pathogens are the leading cause of human illnesses. The detection of foodborne pathogenic bacteria has become a research hotspot in recent years. Rapid detection methods based on immunoassay, molecular biology, microfluidic chip, metabolism, biosensor, and mass spectrometry have developed rapidly and become the main methods for the detection of foodborne pathogens. This study reviewed a variety of rapid detection methods in recent years. The research advances are introduced based on the above technical methods for the rapid detection of foodborne pathogenic bacteria. The study also discusses the limitations of existing methods and their advantages and future development direction, to form an overall understanding of the detection methods, and for point-of-care testing (POCT) applications to accurately and rapidly diagnose and control diseases.